CNVs in human genomes - Ponting, Chris (Henry Stewart Talks, 2009)
Evolution of copy number variants, Positive or negative selection acting on copy number variable genes, Hill-Robertson interference and its effect on the efficacy of selection, Prediction of genes more likely, when copy number variable, to contribute to human disease